The Development of Activity Packages to Promote the Active Aging for the Elderly, the Homebody Group, Nam Jo Sub-District, Mae Tha District, Lampang Province - Punyamoonwongsa, Charunrak; Chanpala, Panisara; Mata, Chatsuda; Chuajedton, Angkhana; Boonklin, Wimwipa; Netasit, Ammaret (Journal of Behavioral Science for Development, 2022)
The objectives of this quasi experiment were to develop an activity package to promote the active aging for the elderly, the homebody group, and study the effect of its implementation. The sample consisted of the elderly, the homebody group aged 60 years and over, living in Nam Jo Sub-district, Mae Tha District, Lampang Province, amounting to 30 people, acquired by volunteer selection. The research tools consisted of 1) the active aging measurement model for the elderly, the homebody group, and 2) activity packages to promote the active aging for the elderly, the homebody group. The statistics employed for analysis were means, standard deviation (S.D.) and paired sample t-test. The research results showed that 7 activities to promote the Active Aging for the Elderly, the Homebody Group with an average score of each item in the range of 4.73-4.90, and the mean of all activities was 4.82 at the most appropriate level. Furthermore, the elderly had higher mean scores for the Active Aging after the experiment than before, with the highest mean scores on participation, followed by health, and security, respectively.